STRATEGI PENGOLAHAN TANAH DALAM MENDUKUNG BUDIDAYA NILAM YANG BERKELANJUTAN DI ACEH BESAR: SOIL MANAGEMENT STRATEGIES TO SUPPORT SUSTAINABLE PATCHOULI CULTIVATION IN ACEH BESAR - Hifnalisa Hifnalisa; Yaumil Khairiyah; Manfarizah Manfarizah; Raichan Izzati; Syaifullah Muhammad; Friesca Erwan; Muhibbuddin Muhibbuddin (LPPM Universitas Abdurrab, 2025)
This community service program aims to develop a sustainable and environmentally friendly patchouli (Pogostemon cablin Benth.) cultivation system in Teuladan Village, Aceh Besar District. The methods applied include minimum tillage, a planting distance of 100 × 100 cm, planting holes of 30 × 30 × 30 cm, the application of compost at 20 tons per hectare two weeks before planting, and subsequent fertilization using urea (500 kg/ha), SP-36 (250 kg/ha), and KCl (500 kg/ha). Patchouli seedlings were sourced from the Patchouli Industry Center in Lhoong Subdistrict and distributed to farmers in quantities of 1,500–2,500 seedlings per person, depending on the available land area. The results of the program showed that this method supported optimal early plant growth, improved the physical and chemical properties of the soil, and enhanced farmers’ participation and understanding of sustainable cultivation practices. This approach has the potential to be replicated in other areas with similar agroecosystems, supporting the sustainable community-based development of patchouli as a commodity.